Nephropathologie infektiöser Erkrankungen - Büttner-Herold, Maike; Amann, Kerstin Ute; Velden, Joachim (Die Pathologie, 2024)
Infections can affect the kidney via different pathways. Urinary tract infections can directly involve the renal tissue by spreading along pre-existing canalicular structures. Such an ascending infection can manifest as a highly active and purulent or even abscessing interstitial nephritis or as a chronic-fibrosing process in recurrent pyelonephritis. Viral infections can also use the canalicular route as in polyomavirus nephropathy or spread via the blood stream in a hematogenous manner as in the case of cytomegalovirus or hantavirus infections. Likewise, bacterial infections can reach the kidney via the blood in the case of systemic infection. Another large group of nephropathies taking place as a sequel of infections includes infection-related glomerulonephritides (IRGN), which are mediated by a series of immunological mechanisms. These IRGN can be subdivided according to their temporal association with the infectious process, occurring either after the infection has healed (postinfectious) or accompanying the ongoing infectious process (parainfectious). The latter, in particular, is of increasing importance in the daily practice of nephropathologists, especially in older patients. A number of other glomerulonephritis forms, i.e., membranous or membranoproliferative forms, can occur as a consequence of infection. In addition, infections can trigger nephropathies, such as thrombotic microangiopathy. The present article gives an overview of morphologic changes in renal parenchyma that take place as a consequence of infectious processes, with particular focus on IRGN.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Immune complex; Infection-related glomerulonephritis; Path of infection; Pathogen spectrum; Urinary tract infection